Air pollution control through biotrickling filters: a review considering operational aspects and expected performance. (1st November 2016) - Schiavon, Marco; Ragazzi, Marco; Rada, Elena Cristina; Torretta, Vincenzo
Abstract: The biological removal of pollutants, especially through biotrickling filters (BTFs), has recently become attractive for the low investment and operational costs and the low secondary pollution. This paper is intended to investigate the state of the art on BTF applications. After an overview on the biodegradation process and the typical parameters involved, this paper presents the analysis of a group of 16 literature studies chosen as the references for this sector. The reference studies differ from one another by the pollutants treated (volatile organic compounds [VOC], hydrogen sulphide, nitrogen oxides and trimethylamine), the geometry and size of the BTFs, and the procedures of the tests. The reference studies are analyzed and discussed in terms of the operational conditions and the results obtained, especially with respect to the removal efficiencies (REs) and the elimination capacities (ECs) of the pollutants considered. Empty bed residence time (EBRT), pollutant loading rate, temperature, pH, oxygen availability, trickling liquid flow rate, inoculum selection and biomass control strategies revealed to be the most important operational factors influencing the removal performance of a BTF.